2006
DOI: 10.1007/s10803-006-0119-9
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization and Expenditures for Children with Autism: Data from U.S. National Samples

Abstract: Little is known about the use of medical services by children who have autism (ASD). Provide nationally representative data for health service utilization and expenditures of children with ASD. Cross-sectional survey using the Medical Expenditure Panel (MEPS), and National (Hospital) Ambulatory Medical Care Surveys (N(H)AMCS). A total of 80 children with ASD were identified from N(H)AMCS (weighted sample size (wss) 186,281), and 31 (wss 340,158) from MEPS. They had more outpatient visits, physician visits, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
175
5
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(188 citation statements)
references
References 26 publications
7
175
5
1
Order By: Relevance
“…In a nationally representative sample, it was found that children with ASDs spent twice as much time with the physician per outpatient visit compared with children in control groups. 89 …”
Section: Medical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nationally representative sample, it was found that children with ASDs spent twice as much time with the physician per outpatient visit compared with children in control groups. 89 …”
Section: Medical Managementmentioning
confidence: 99%
“…Health care utilization and costs are substantially higher for children and adolescents with ASDs compared with children without ASDs, [89][90][91] and available data suggest that mortality is increased as well (standardized mortality ratio: 2.4 -2.6). 92,93 The increased mortality in ASDs is thought to be largely, but not completely, accounted for by the increased mortality associated with mental retardation and epilepsy.…”
Section: Associated Morbidity and Mortalitymentioning
confidence: 99%
“…[6][7][8][9][10][11][12] In addition, CSHCN with more severe medical conditions or who require more intensive services often face different challenges in their transition to adult health care, partly because of the nature of and costs associated with the services required. [13][14][15][16] In recognition of the importance of transition services, the Maternal and Child Health Bureau (MCHB) of the Health Resources and Services Administration added "receipt of the services necessary to make transitions to all aspects of adult life" as 1 of 6 system indicators to measure state and national progress toward implementing community-based systems of services for CSHCN. 17 The 2005-2006 National Survey of Children With Special Health Care Needs (NS-CSHCN) was developed to provide state and national prevalence estimates for assessing progress toward federal and state objectives and to inform state Title V needs assessments.…”
mentioning
confidence: 99%
“…Researchers have assessed use and cost of health care for children with ASD (e.g. Croen et al, 2006;Liptak, et al, 2006), and have developed broader measures that account for the indirect as well as the direct costs associated with ASD (e.g. Ganz, 2006Ganz, , 2007.…”
Section: Total Cost Of Autism: Estimates and Issuesmentioning
confidence: 99%